(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
We studied 14 healthy young men participating in an experiment that induced acute severe normobaric hypoxia at rest (breathing a hypoxic gas mixture with 9% O2 by volume); the measurements occurred during 25 minutes of hypoxia and for 15 minutes of the early recovery period. Using a statistical analysis method, we divided the experimental group into 2 subgroups with different nitric oxide(NOx) values. The healthy men with significantly higher basal NOx levels also demonstrated higher plasma NOx concentrations during the hypoxic exposure and in the recovery period. The participants in this group also had significantly lower plasma lactate levels both before and during the experiment. We assumed that individual NO levels should be taken into consideration when assessing lactate indices in subjects under short-term acute normobaric hypoxia.